Linking small fruit and vegetable farmers and institutional foodservice operations: marketing challenges and considerations. Issue 3 (12th February 2018) - Boys, Kathryn A.; Fraser, Angela M.
Abstract: The centralized nature of the United States food production, processing and distribution system makes it difficult for small fruit and vegetable farmers to serve as suppliers to institutional foodservice operations (IFOs), such as schools and hospitals. Due to age, economic and/or health status, it is often the clients of these foodservice operations who would benefit from increasing their consumption of locally grown fruits and vegetables. Unfortunately, institutions are often limited in their resources and food preparation infrastructure, and lack market-based incentives to incorporate locally grown foods into their menus. This study identifies and suggests solutions to barriers that limit the ability of small fruit and vegetable farmers to serve as suppliers to IFOs. Data were collected through an extensive series of focus group meetings held with small-scale fruit and vegetable farmers in three South-Atlantic states. From these meetings, practical marketing considerations, such as payment terms, and processing, packaging and delivery requirements of supplying institutional foodservice buyers, were identified as obstacles to the efficient function of this market channel. Food safety challenges, including the related issues of obtaining (food) products liability insurance and food safety certifications, were also acknowledged among top concerns. A majority of the identified challenges were similar to those reported in other studies, but several were complicated by characteristics of farm production, limited food system infrastructure and marketing experiences in the study region. Several practical solutions to overcoming some of these marketing constraints are offered.